Now is the time! Confronting neo-liberalism in early childhood. (March 2022) - Moss, Peter; Roberts-Holmes, Guy
Over the last 30 years, neo-liberalism has permeated early childhood, as all other aspects of life. Having introduced what neo-liberalism is, the article looks at some of its effects on early childhood education and care, including markets, imaginaries and governance. It argues that though neo-liberalism is a powerful force, it is resistible and replaceable – and that now is the time to be developing alternatives to existing policies, grounding them in ideas that contest neo-liberalism.